Extent of knowledge and adoption of recommended wheat production practices among wheat growers in Malwa Region (M.P.) - Jat, Mangi Lal; Jaiswal, D.K.; Saharawat, Yashpal Singh (ACS Publisher, 2022)
Wheat is an important source of nutrition in our staple diet. Although farmers in northern India are growing wheat for a long time many farmers are lacking good knowledge of wheat and its new varieties production practices. The study was conducted to know the extent of knowledge and adoption of recommended wheat production practices among wheat cultivating farmers of the Malwa region. Nine farmers (3 big, 3 medium and 3 small farmers) were selected randomly from each (thirty-six) selected village of nine blocks of Hosangabad, Hadra and Sehore districts making a total of 324 wheat growers. Among the practicewise level of knowledge regarding recommended wheat production technology; method of storage (mean score- 2.30) was ranked first and selection and preparation of land (mean score-2.25) was ranked second. On the whole, the highest number of the wheat growers (46.29%) had a medium knowledge level of recommended wheat production practices while 41.66%had a medium level of adoption on the basis of their level of adoption of recommended technological practices of wheat crop cultivation.